Effect of different gamma radiation doses on the germination and seedling growth of wheat and triticale cultivars - Di Pane, Francisco; Lopez, Silvia Concepción; Cantamutto, Miguel Angel; Domenech, Marisa Beatriz; Castro Franco, Mauricio (Southern Cross Publishing, 2020)
Plant breeding of wheat and triticale in Argentina is based on the objective of improving an individual crop, with respect to resistance to drought stress. The use of gamma radiation holds promise for physiological crop improvement. The objective of this study was to determine and compare the effect of different gamma radiation doses on the germination and seedling growth of Argentine wheat and triticale cultivars. Seeds of wheat cv. Baguette 10 and triticale cv. Espinillo INTA were irradiated at doses of 0, 50, 200, 400, 550, 700, 850 and 1000 Gy s-1. The final germination percentage (FGP), sprout length (SL) and median lethal dose (LD50) were used as metrics of germination, seedling growth and lethal dose, respectively. Two experimental designs were used. First, a completely randomized factorial was used to compare the effect of the doses within species by using ANOVA; second, a completely repeated measures design was used to evaluate the effect of days after germination on plant survival by species using a mixed linear model. The results suggest that at the early germination stage, gamma radiation limited root growth and stem length. The FGP of wheat seeds was significantly affected by gamma radiation at a dose of 550 Gy, whereas triticale seeds were significantly affected at a dose of 700 Gy. The SL of both species was similarly affected at 50 Gy. The stem mortality of wheat and triticale seeds increased at an increasing gamma radiation dose and days after germination. Finally, the LD50 value for wheat and triticale seeds was ~450 Gy. These results might be useful to set a benchmark of the effect of the gamma radiation dose to induce mutations in wheat and triticale seeds from Argentine cultivars.